Eine Marien-Elegie vom Hof Kaiser Maximilians I.: der Text von Heinrich Isaacs Motette "O decus ecclesiae" - Bauer-Zetzmann, Martin (Classica et Mediaevalia, 2022)
This paper aims to revise and reconstruct the highly corrupt text of Heinrich Isaac’s Marianic motet O decus ecclesiae by examining the only manuscript source anew. It can be demonstrated that the text is written in elegiac distichs and artfully blends Christian ideas and classicising language. It is therefore highly probable that its author was one of the leading humanist poets at the court of Emperor Maximilian I and that the elegy was commissioned for a representative event.